Analisis Faktor-Faktor Yang Mempengaruhi Mahasiswa Dalam Pemilihan Karir Sebagai Akuntan Publik (Studi Empiris Pada Perguruan Tinggi Swasta Di Surakarta) - Bere Laka, Jesi Kristin P (IAIN Surakarta, 2019)
The aim of this study is to analyse factors affecting students in career selection as a public accountant study of S1 accounting students of private colleges in Surakarta. The population of this study were all students S1 accounting students of 14 private universities in Surakarta in the 2015 and 2016 classes. Total populations are 3.830. Sample of this study are 100 respondents, selected by proportionate random Sampling method. The analysis method of this study is multiple regres- sion method. The results of this study are: 1) Financial rewards/salary does not affect the career choice of students as public accountants. 2) Job market considerations do not affect the career choice of students as pub- lic accountants. 3) Professional recognition has a significant positive effect on student career choice as a public accountant. 4) Social values have a significant positive effect on the career choice of students as publik accountants. 5) Personality does not influence the career choice of students as public accountants. Keywords: Financial Reward/Salary, Job Market Considerations, Professional Recognition, Social Values, Personality JEL Classification: O15, L84, I21, I24